EU Water Policy: Pollution source control by water companies in England and Wales - Spiller, Marc (Cranfield University, 2010)
Water management is undergoing a transformation towards integration, source control and ecological thinking. In the EU, the Water Framework Directive can be considered as a driver towards this new approach to water management. Innovations are deemed necessary to deliver this ideal of water management. In this thesis efforts by water sewerage companies in England & Wales to rectify agricultural pollution at source are viewed as an organisational innovation towards more sustainable water management. These source control interventions can help achieving the goals of the Water Framework Directive by reducing diffuse pollution from agriculture, fostering participation in water management and by reducing overall cost of implementation. This thesis contributes to understanding the process of change in water management by developing a model of the innovation-decision process. Insights about how innovation and therefore change can be influenced is generated by applying this model to the process of source control intervention adoption by water and sewerage companies. This research employed a flexible research design using comparative case studies. Each of the 10 water and sewerage companies in England and Wales represented an individual case. Data were collected in two phases using semi-structured interviews with selected water and sewerage company representatives. Thematic analysis, recurrence counts and content analysis were applied to analyse interviews. It was found that water companies are likely to contribute towards integrated approaches to water management, since there is a trend to adopt source control intervention. Change in water management is influenced by the interaction of factors from the domains: ‗Natural-Physical‘, ‗Organisational Characteristics‘, ‗Regulatory- Institutional‘ and ‗Innovation Attributes‘. The rate of change by water and sewerage companies is governed by a combination of asset characteristics, environmental state changes and the funding cycle. Furthermore, innovation is triggered by direct regulation and regulation that requires the gathering of information. Contrary to this flexible or framework regulation performs better in guiding the direction of change.
Keywords: factors; catchment; innovation; flexible design; water framework directive